Meningkatkan Motivasi Belajar Siswa pada Pelajaran PKN di Sekolah Dasar dengan Media Quizizz - Iswara Sampia; Adrias adrias; Salmaini Safitri Syam (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
The purpose of this study is to examine how using the Quizizz app can enhance students' learning results when Pancasila and Civic Education (PPKn) is taught at the primary school level. In addition to emphasizing memorization, PPKn education is supposed to foster character development by imparting Pancasila principles like justice, tolerance, and cooperation. Additionally, this study seeks to investigate how appropriate learning materials can improve students' willingness to learn, which has a direct impact on their academic performance. Students can actively study and get quick feedback by utilizing Quizizz, a web-based tool that offers dynamic and captivating tests.